THE DEVELOPING LOCAL CURRICULUM ACCORDING TO THE MARITIME ZONE CURRICULUM IN THAILAND OF WAT MUKTHARA SCHOOL UNDER NAKHON SI THAMMARAT PIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Promkaew, Pakdee; PhrakhruPrachotkichchaporn; Weeraponkan, Boonlert; NanaKhon, Apijit (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research were: 1) to study the status of the local curriculum at Wat Mukthara School, 2) to develop a local curriculum on Thailand’s maritime zones for Wat Mukthara School, and 3) to evaluate the local curriculum based on Thailand’s maritime zones for Wat Mukthara School. This study employed qualitative research methodology. The process included three phases: 1) studying the current state of the curriculum through in-depth interviews with 15 key informants, 2) developing the curriculum through in-depth interviews with 5 key informants, and 3) evaluating the curriculum with 15 experts. Data were analyzed using inductive analysis. The research findings revealed that: 1) The existing local curriculum at Wat Mukthara School was not comprehensive in addressing the community’s context, nor did it meet the needs of students, parents, and the community. The teaching and learning activities lacked engagement, and the curriculum documents were incomplete, with content that was inappropriate for students and the community. 2) The curriculum development process consisted of six stages: (1) studying and analyzing fundamental data, (2) designing and drafting the curriculum, (3) preparing curriculum documents, (4) reviewing and piloting the curriculum, (5) implementing the curriculum, and (6) evaluating the curriculum. The key components of the local curriculum included: (1) curriculum significance, (2) vision, (3) objectives, (4) mission, (5) core competencies of learners, (6) desirable characteristics, (7) content structure, (8) subject structure, (9) learning assessment forms, (10) assessment and evaluation criteria, (11) additional learning resources. 3) The curriculum evaluation indicated that the curriculum was appropriate, feasible, beneficial, and accepted by relevant organizations. The curriculum was beneficial to the local community and aligned with the context of the school, which is located in a coastal area.